2016
DOI: 10.1586/17476348.2016.1157472
|View full text |Cite
|
Sign up to set email alerts
|

Changes in structural and metabolic muscle characteristics following exercise-based interventions in patients with COPD: a systematic review

Abstract: Patients with COPD suffer from lower-limb muscle dysfunction characterized by lower muscle oxidative capacity and muscle mass. Exercise-based training is expected to attenuate lower-limb intramuscular characteristics, but a detailed systematic approach to review the available evidence has not been performed yet. PUBMED and PEDro databases were searched. Twenty-five studies that implemented an exercise-based training program (aerobic and/or resistance training, high intensity interval training, electrical or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 80 publications
7
36
0
Order By: Relevance
“…Comparing the effect on endurance and resistance training on muscle inflammation, Ryrso et al (2018) found that both training modalities did not alter the content of proinflammatory cytokines and inflammatory cells. This suggests that exercise-based interventions, at least, does not worsen muscle inflammation (De Brandt et al, 2016) -if present (see section"Inflammation"). This assertion should be tempered with the findings of Menon et al (2012b) who reported that 8 weeks of high-intensity resistance training resulted in a large reduction (↓100%) of exercise-induced neutrophils in the quadriceps.…”
Section: Muscle Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the effect on endurance and resistance training on muscle inflammation, Ryrso et al (2018) found that both training modalities did not alter the content of proinflammatory cytokines and inflammatory cells. This suggests that exercise-based interventions, at least, does not worsen muscle inflammation (De Brandt et al, 2016) -if present (see section"Inflammation"). This assertion should be tempered with the findings of Menon et al (2012b) who reported that 8 weeks of high-intensity resistance training resulted in a large reduction (↓100%) of exercise-induced neutrophils in the quadriceps.…”
Section: Muscle Inflammationmentioning
confidence: 99%
“…Exercise training has only limited beneficial effect on markers of oxidative and nitrosative stress in patients with COPD (De Brandt et al, 2016). In fact, several studies have shown an unchanged antioxidant capacity following aerobic (Barreiro et al, 2009) and high-intensity interval training [e.g., ∼ 90% peak work rate (WR peak ) (Rabinovich et al, 2001)]; of note, antioxidant capacity was improved in healthy subjects after the same intervention (Rabinovich et al, 2001;Barreiro et al, 2009).…”
Section: Oxidative Stress and Antioxidant Capacitymentioning
confidence: 99%
“…survival, exercise capacity, muscle strength, quality of life) 86,87 through benefits from muscle structural and functional changes in response to both training modalities. The effects on muscle structure are an increase in fibre size and capillarisation, without significant results on metabolic characteristics and oxidative stress 88 . However, the studies combining resistance with aerobic exercise training that explored changes at structural level used different strategies of training.…”
Section: Aerobic and Combined (Aerobic And Resistance) Trainingmentioning
confidence: 99%
“…However, the studies combining resistance with aerobic exercise training that explored changes at structural level used different strategies of training. More trials are needed to investigate these physiological and structural changes in the muscle after PR programmes 88 .…”
Section: Aerobic and Combined (Aerobic And Resistance) Trainingmentioning
confidence: 99%
“…For individuals suffering from chronic obstructive lung disease (COPD), physical exercise is a prerequisite for adequate treatment and rehabilitation. It counteracts the muscle pathophysiology inherent to the disease and improves health‐related quality of life and activities of daily living . Unfortunately, exercise training is a demanding task for such patients.…”
Section: Introductionmentioning
confidence: 99%